Kooperative Regelungskonzepte auf Basis der Spieltheorie und deren Anwendung auf Fahrerassistenzsysteme - Flad, Michael (Karlsruher Beiträge zur Regelungs- und Steuerungstechnik / Karlsruher Institut für Technologie, Institut für Regelungs- und Steuerungssysteme, 2017)
Cooperative control loops in which human and a technical automation system perform a control task in close cooperation are investigated. A control framework is proposed which is based on a formal description of the cooperative control problem. The main idea of the control algorithm is to solve a differential game on a sliding horizon. The concept has been applied to design two cooperative advanced driver-assistance systems. One for the longitudinal driving task, one for the lateral driving task.